High-wettability lithium ion battery diaphragm and preparation method thereof
The slurry is prepared by dispersing the non-fluorine binder with multiple dispersant and applied to the lithium-ion battery separator using matrix dot coating technology, which solves the problem of insufficient wettability of the separator electrolyte and achieves higher battery efficiency and safety.
Patent Information
- Application Number
- CN202411790192.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The electrolyte of the existing lithium-ion battery separator is insufficient, which affects the overall performance and service life of the battery.
The slurry is prepared by dispersing a multi-dispersant non-fluorine binder, and is coated on the base film by matrix dot coating technology to form a highly wettable coating.
It significantly improves the electrolyte wetting of the lithium-ion battery separator, enhances the overall performance and stability of the battery, extends the service life of the battery, and improves the safety of the battery.
Smart Images

Figure BDA0005175132250000101 
Figure BDA0005175132250000102 
Figure BDA0005175132250000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a high-wettability lithium-ion battery separator and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have high energy density and long life. They are an important technical means of modern energy storage and are widely used in electric vehicles, portable electronic devices, energy storage systems and other fields. However, the safety and electrolyte wettability of lithium-ion batteries are key factors affecting their performance and service life. In the manufacturing process of lithium-ion batteries, the diaphragm, as an important component of the battery, plays the role of isolating the positive and negative electrodes and preventing short circuits. At the same time, the diaphragm also needs to have good electrolyte wettability to ensure that ions can be smoothly transmitted through the diaphragm, thereby improving the overall efficiency and stability of the battery. Therefore, improving the wettability of the diaphragm is of great significance to improving the performance of lithium-ion batteries. Summary of the invention
[0003] In view of the deficiencies of the prior art, an object of the present invention is to provide a highly wettable lithium-ion battery separator.
[0004] Another object of the present invention is to provide a method for preparing the above-mentioned high wettability lithium-ion battery separator.
[0005] Another object of the present invention is to provide a slurry.
[0006] Another object of the present invention is to provide a method for preparing the above slurry, wherein the method disperses the non-fluorine binder by multiple dispersants to obtain the slurry.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A highly wettable lithium-ion battery separator comprises a base film and a coating on the base film, wherein the coating comprises polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol, wherein the ratio of polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1-5):(1-5):(160-180):(180-200):(180-200) by weight.
[0009] In the above technical scheme, the ratio of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is preferably (2-5):(2-5):(170-180):(190-200):(190-200) by mass.
[0010] In the above technical solution, the thickness of the coating is 4 to 5 microns.
[0011] The method for preparing the highly wettable lithium-ion battery separator comprises: applying the slurry on the base film by spot coating, drying, obtaining a coating on the base film, and obtaining the highly wettable lithium-ion battery separator.
[0012] A slurry comprises: water, a dispersant and a non-fluorine binder, wherein the dispersant is a mixture of polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate and sodium carboxymethyl cellulose, and the non-fluorine binder is a mixture of polyacrylonitrile and polyvinyl alcohol. Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1600-2400):(1-5):(1-5):(160-180):(180-200):(180-200).
[0013] In the above technical scheme, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is preferably (2000-2400): (2-5): (2-5): (170-180): (190-200): (190-200) by mass.
[0014] The method for preparing the above slurry comprises the following steps:
[0015] Step 1, mixing water and polyvinyl pyrrolidone, emulsifying, and obtaining a first substance;
[0016] Step 2, mixing the first substance and sodium dodecyl diphenyl ether disulfonate, emulsifying, and obtaining a second substance;
[0017] Step 3, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, to obtain a third substance;
[0018] Step 4, mixing the third substance and polyacrylonitrile, emulsifying, to obtain a fourth substance;
[0019] Step 5, mixing the fourth substance and polyvinyl alcohol, emulsifying, and obtaining a slurry;
[0020] The emulsification conditions in step 1 to step 3 are: stirring at 50 to 60° C. and vacuum environment for 15 to 30 minutes, and the emulsification conditions in step 4 to step 5 are: stirring at 50 to 60° C. and vacuum environment for 20 to 30 minutes.
[0021] In steps 1 to 3, the emulsification conditions are: stirring for 15 to 30 minutes at a rotation speed of 1800 to 2000 r / min and a revolution speed of 40 to 50 r / min at 50 to 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 to -0.08 MPa.
[0022] In steps 4 and 5, the emulsification conditions are: stirring for 20 to 30 minutes at a rotation speed of 2500 to 2800 r / min and a revolution speed of 42 to 52 r / min at 50 to 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.09 to -0.08 MPa.
[0023] In the method for preparing a slurry, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1600-2400): (1-5): (1-5): (160-180): (180-200): (180-200), preferably: in parts by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is preferably (2000-2400): (2-5): (2-5): (170-180): (190-200): (190-200).
[0024] Application of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol in synergistically improving the wettability of diaphragms.
[0025] Application of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol in synergistically improving the liquid absorption rate, liquid retention rate and / or ion conductivity of the diaphragm.
[0026] After water and polyvinyl pyrrolidone (non-ionic dispersant) are emulsified, the solubility of water-soluble organic matter is increased, and then sodium dodecyl diphenyl ether disulfonate (anionic dispersant) is added to make the system have more beneficial surface activity and solubilization. After adding sodium carboxymethyl cellulose, the viscosity and stability of the system are increased. The above dispersants are added in sequence to enhance the solubility and surface activity of the system, which is more beneficial to the subsequent dissolution of the organic binder and makes the system more uniform. Then polyacrylonitrile is added, and finally polyvinyl alcohol is added. The hydroxyl groups in the polyvinyl alcohol chain segment increase the van der Waals force of the system, thereby further enhancing the stability of the slurry.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. Improve the wettability of the diaphragm: The slurry is prepared by a reasonable ratio of multiple dispersants and two non-fluorine binders, combined with matrix dot coating, which effectively reduces the surface tension of the liquid, making it easier for the liquid to penetrate into the diaphragm, and significantly improves the electrolyte wettability of the lithium-ion battery diaphragm. Good wettability helps to improve ion transmission efficiency, reduce internal resistance, and thus improve the overall performance and stability of the battery.
[0029] 2. Enhanced safety: Non-fluorine binders have lower surface energy, which makes it easier to bond with the base film, helping to improve the safety of lithium-ion batteries, reduce the risks of overcharging, over-discharging, short circuit and thermal runaway, and ensure user safety.
[0030] 3. Extending battery life: The slurry of the present invention is combined with a spot coating method, so that the slurry is evenly coated on the surface of the base film, avoiding the phenomenon of the coating being too thick or too thin locally, thereby improving the air permeability of the diaphragm and extending the service life of the lithium-ion battery.
[0031] 4. Enhanced liquid retention capacity: The coating of the present invention is a non-fluorinated organic coating with high hydrophilicity, which makes the diaphragm have good wettability and good liquid retention capacity for the electrolyte in the lithium-ion battery, making it less likely for the electrolyte to be lost during the battery charging and discharging process.
[0032] 5. Environmental friendliness: Non-fluorinated coatings are more environmentally friendly compared to fluorinated coatings.
[0033] 6. The present invention adopts matrix dot coating, which makes the coating process more precise and controllable, and improves production efficiency and product quality. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0035] Polyvinylpyrrolidone: light yellow powder, density is about 1.144g / cm 3 . Boiling point is 217.6℃, melting point is 130℃. Flash point is 93.9℃, number average molecular weight (Mn) is 8971g / mol, Shanghai Dibai Chemical Technology Co., Ltd.
[0036] Sodium dodecyl diphenyl ether disulfonate: chemical formula is C 24 H 32 O7S2Na2, molecular weight is 542.6, purity is 99.0%, density is about 1.161g / ml (at 25℃), viscosity is 145MPa·s at 25℃ and concentration is 0.1%, Tianjin Xiensi Biochemical Technology Co., Ltd.
[0037] Sodium carboxymethyl cellulose: light yellow powder, viscosity 400-800 cP (2% soluble in water test at 25°C), produced by Bid Pharmaceutical Co., Ltd., Pudong New Area, Shanghai.
[0038] Polyacrylonitrile: White opaque powder. Density: 1.184 g / mL at 25℃ (lit.). Melting point: 317℃. Glass transition temperature: 85℃. Number average molecular weight (Mn) is 34369 g / mol, TCI Chemicals Co., Ltd.
[0039] Polyvinyl alcohol: The relative density (25°C) of polyvinyl alcohol is 1.29 (solid), and the number average molecular weight (Mn) is 100967 g / mol, Changzhou Qidi Chemical Co., Ltd.
[0040] The test standard for liquid absorption rate and liquid retention rate is QB / T 2303.11-2008, the test standard for wettability is QB / T2303.11-2008, the test standard for contact angle is GB / T 30693-2014, and the test standard for ionic conductivity is GB / T36363-2018.
[0041] In the following examples, the temperature for testing ionic conductivity is 40° C. and the relative humidity is 45-50%.
[0042] Air permeability value added: diaphragm air permeability value - basement membrane air permeability value.
[0043] In the following embodiments, the base film is a wet-process polyethylene film, the thickness of the base film is 7.1 μm, and the air permeability is 71 Sec / 100 ml. In the present invention, the thickness and air permeability are tested in accordance with GBT 36363-2018.
[0044] In the following examples, wettability characterizes the affinity between the diaphragm and the electrolyte. The larger the wettability value, the better the wettability and the stronger the liquid absorption and retention, which can make the battery internal resistance lower. The calculation formula of wettability v is: v = h / t, where h is the wetting height (the height of the electrolyte penetrating in the vertical direction of the diaphragm), in mm, and t is the wetting time, in min.
[0045] The electrolyte used in the contact angle test and wettability test is a mixture of an electrolyte and a solvent. The electrolyte in the electrolyte is lithium hexafluorophosphate, and the solvent in the electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1). The concentration of the electrolyte in the electrolyte is 1 mol / L.
[0046] Peel strength test: Cut the membrane into test samples of 3cm*15cm size, stick 3M peeling tape (2.6cm*15cm) in the middle of the coating surface of the membrane, roll the test sample with a 2kg roller (roll forward 4 times to ensure that the entire test sample is rolled in place, rolling in the same direction, and cannot be rolled back and forth), tear off 5cm of one end of the 3M peeling tape, clamp the 3M peeling tape and the membrane straight in the upper and lower clamps of the Shimadzu intelligent electronic tensile testing machine, and test to obtain the peel strength. The calculation formula for peel strength is: average force value (N) / peeling tape width (cm)*100%. Name and model of testing equipment: Shimadzu intelligent electronic tensile testing machine AGS-100N, 3M tape: 3M Scotch 600 (26mm wide). Shimadzu intelligent electronic tensile testing machine AGS-100N: maximum load: 100N, test speed: 100mm / min. In the following embodiments, water is deionized water.
[0047] Examples 1-2, Example 4 and Comparative Example 1
[0048] A method for preparing a slurry comprises the following steps:
[0049] Step 1, water and polyvinyl pyrrolidone are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain a first substance, and the emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000r / min and a revolution speed of 40r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08Mpa;
[0050] Step 2, adding sodium dodecyl diphenyl ether disulfonate to the first substance, emulsifying, and obtaining a second substance, wherein the emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 Mpa;
[0051] Step 3, adding sodium carboxymethyl cellulose to the second substance, emulsifying, and obtaining a third substance, wherein the emulsifying conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 Mpa;
[0052] Step 4, adding polyacrylonitrile to the third substance, emulsifying, to obtain a fourth substance, the emulsification conditions being: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment being -0.09 Mpa;
[0053] Step 5, adding polyvinyl alcohol to the fourth substance, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0054] The ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is X in parts by mass.
[0055] The X values are shown in Table 1.
[0056] Table 1
[0057] Slurry X Example 1 2400:5:5:180:200:200 Example 2 1600:1:1:160:180:180 Example 4 2400:1:1:160:180:180 Comparative Example 1 2400:10:5:180:200:200
[0058] Example 3
[0059] A method for preparing a slurry comprises the following steps:
[0060] Step 1, water and polyvinyl pyrrolidone are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain a first substance, and the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1800r / min and a revolution speed of 50r / min at 50°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095Mpa;
[0061] Step 2, adding sodium dodecyl diphenyl ether disulfonate to the first substance, emulsifying, and obtaining a second substance, wherein the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1800 r / min and a revolution speed of 50 r / min at 50° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa;
[0062] Step 3, adding sodium carboxymethyl cellulose to the second substance, emulsifying, and obtaining a third substance, wherein the emulsifying conditions are: stirring for 30 minutes at a rotation speed of 1800 r / min and a revolution speed of 50 r / min at 50° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa;
[0063] Step 4, adding polyacrylonitrile to the third substance, emulsifying, to obtain a fourth substance, the emulsification conditions being: stirring for 20 minutes at a rotation speed of 2500 r / min and a revolution speed of 42 r / min at 50° C. and in a vacuum environment, the vacuum degree of the vacuum environment being -0.08 Mpa;
[0064] Step 5, adding polyvinyl alcohol to the fourth substance, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 20 minutes at a rotation speed of 2500 r / min and a revolution speed of 42 r / min at 50° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.08 MPa;
[0065] Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is 2200:3:3:170:190:190.
[0066] Comparative Example 2 (without addition of polyvinyl pyrrolidone and sodium dodecyl diphenyl ether disulfonate)
[0067] A method for preparing a slurry comprises the following steps:
[0068] Step 1, water and sodium carboxymethyl cellulose are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain substance A1. The emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and a vacuum degree of the vacuum environment of -0.08 MPa;
[0069] Step 2, adding polyacrylonitrile to substance A1, emulsifying to obtain substance A2, the emulsifying conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0070] Step 3, adding polyvinyl alcohol to substance A2, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0071] The ratio of water, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is 2400:180:200:200 in parts by mass.
[0072] The slurry prepared in Comparative Example 2 has poor stability and cannot be coated.
[0073] Comparative Example 3 (without addition of sodium carboxymethyl cellulose)
[0074] A method for preparing a slurry comprises the following steps:
[0075] Step 1, water and polyvinyl pyrrolidone are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain a first substance, and the emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000r / min and a revolution speed of 40r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08Mpa;
[0076] Step 2, adding sodium dodecyl diphenyl ether disulfonate to the first substance, emulsifying, and obtaining a second substance, wherein the emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 Mpa;
[0077] Step 3, adding polyacrylonitrile to the second substance, emulsifying, and obtaining substance Y, wherein the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.09 Mpa;
[0078] Step 4, adding polyvinyl alcohol to substance Y, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0079] Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, polyacrylonitrile and polyvinyl alcohol is 2400:5:5:200:200.
[0080] The slurry prepared in Comparative Example 3 has poor stability and cannot be coated.
[0081] Comparative Example 4 (without addition of polyvinyl pyrrolidone)
[0082] A method for preparing a slurry comprises the following steps:
[0083] Step 1, water and sodium dodecyl diphenyl ether disulfonate are mixed in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), emulsified to obtain B1 substance, the emulsification conditions are: at 60°C, in a vacuum environment, stirring at a rotation speed of 2000r / min and a revolution speed of 40r / min for 15min, and the vacuum degree of the vacuum environment is -0.08Mpa;
[0084] Step 2, adding sodium carboxymethyl cellulose to substance B1, emulsifying to obtain substance B2, the emulsifying conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.08 Mpa;
[0085] Step 3, adding polyacrylonitrile to substance B2, emulsifying, and obtaining substance B3, the emulsifying conditions being: stirring for 30 min at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment being -0.09 Mpa;
[0086] Step 4, adding polyvinyl alcohol to the B3 substance, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0087] Calculated by mass, the ratio of water, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is 2400:5:180:200:200.
[0088] Comparative Example 5 (without addition of sodium dodecyl diphenyl ether disulfonate)
[0089] A method for preparing a slurry comprises the following steps:
[0090] Step 1, water and polyvinyl pyrrolidone are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain a first substance, and the emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000r / min and a revolution speed of 40r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08Mpa;
[0091] Step 2, adding sodium carboxymethyl cellulose to the first substance, emulsifying, and obtaining substance C1, wherein the emulsifying conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 Mpa;
[0092] Step 3, adding polyacrylonitrile to the C1 substance, emulsifying, and obtaining the C2 substance, the emulsifying conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 Mpa;
[0093] Step 4, adding polyvinyl alcohol to the C2 substance, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0094] Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is 2400:5:180:200:200.
[0095] Comparative Example 6 (without addition of polyvinyl alcohol)
[0096] A slurry, which is the fourth substance prepared in Example 1.
[0097] Comparative Example 7 (without addition of polyacrylonitrile)
[0098] A method for preparing a slurry comprises: adding polyvinyl alcohol to the third substance of Example 1, emulsifying, and obtaining a slurry, wherein the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, and the vacuum degree of the vacuum environment is -0.09 Mpa. In terms of mass fractions, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, and polyvinyl alcohol is 2400:5:5:180:200.
[0099] Comparative Example 8
[0100] A method for preparing a slurry comprises the following steps:
[0101] Step 1, water and sodium carboxymethyl cellulose are mixed and emulsified in a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.) to obtain E1 substance. The emulsification conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and a vacuum degree of the vacuum environment of -0.08 MPa;
[0102] Step 2, adding sodium dodecyl diphenyl ether disulfonate to substance E1, emulsifying to obtain substance E2, the emulsifying conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.08 MPa;
[0103] Step 3, adding polyvinyl pyrrolidone to the E2 substance, emulsifying, and obtaining the E3 substance, the emulsifying conditions are: stirring for 15 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.08 Mpa;
[0104] Step 4, adding polyacrylonitrile to the E3 substance, emulsifying, and obtaining the E4 substance, the emulsifying conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 Mpa;
[0105] Step 5, adding polyvinyl alcohol to the E4 substance, emulsifying to obtain a slurry, the emulsification conditions are: stirring for 30 minutes at a rotation speed of 2800 r / min and a revolution speed of 52 r / min at 60° C. and in a vacuum environment, the vacuum degree of the vacuum environment is -0.09 MPa;
[0106] Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is 2400:5:5:180:200:200.
[0107] Examples 5 to 8 and Comparative Examples 9 to 14
[0108] A method for preparing a lithium-ion battery separator comprises: pumping a slurry into a matrix dot coating structure, coating the slurry on one side (coating on any side of the base film) on the base film by dot coating, drying at 80° C. for 10 min, obtaining a coating on the base film, and obtaining a lithium-ion battery separator. The slurry is one of Examples 1 to 4, Comparative Example 1, and Comparative Examples 4 to 8. The diameter of the coating point on the coating is 330 μm, and the coating points are arranged in a square shape, and the side length of the square is 490 μm. The coating amount is 0.5 g / ㎡.
[0109] Table 2
[0110]
[0111]
[0112] Example 9
[0113] A method for preparing a lithium-ion battery separator comprises: pumping the slurry prepared in Example 1 into a rotary spray coating structure, coating the slurry on one side (coating on either side of the base film) of the base film by spraying, drying at 80° C. for 10 minutes, obtaining a coating on the base film, and obtaining a lithium-ion battery separator. The coating amount is 0.5 g / ㎡.
[0114] The data of the diaphragms prepared in Examples 5 to 9 and Comparative Examples 9 to 14 are as follows (the thickness increment is the thickness of the coating):
[0115] Table 3 (The contact angle in Table 3 is the contact angle of the lithium ion battery separator to the electrolyte)
[0116]
[0117]
[0118] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A highly wettable lithium-ion battery separator, characterized in that: include: The base film and the coating on the base film, the coating includes: polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol, and the ratio of polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1-5):(1-5):(160-180):(180-200):(180-200) by mass.
2. The highly wettable lithium-ion battery separator according to claim 1, characterized in that: In terms of mass fractions, the ratio of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (2-5):(2-5):(170-180):(190-200):(190-200).
3. The highly wettable lithium-ion battery separator according to claim 1, characterized in that: The thickness of the coating is 4 to 5 microns.
4. The method for preparing a highly wettable lithium-ion battery separator according to any one of claims 1 to 3, characterized in that: include: The slurry is coated on the base film by a dot coating method, and then dried to obtain a coating on the base film to obtain a highly wettable lithium-ion battery separator.
5. A slurry, characterized in that: include: Water, a dispersant and a non-fluorine binder, wherein the dispersant is a mixture of polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate and sodium carboxymethyl cellulose, and the non-fluorine binder is a mixture of polyacrylonitrile and polyvinyl alcohol. Calculated by mass, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl oxide disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1600-2400):(1-5):(1-5):(160-180):(180-200):(180-200).
6. The slurry according to claim 5, characterized in that In terms of mass fractions, the ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (2000-2400): (2-5): (2-5): (170-180): (190-200): (190-200).
7. A method for preparing the slurry according to any one of claims 5 to 6, characterized in that: The following steps are involved: Step 1, mixing water and polyvinyl pyrrolidone, emulsifying, and obtaining a first substance; Step 2, mixing the first substance and sodium dodecyl diphenyl ether disulfonate, emulsifying, and obtaining a second substance; Step 3, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, to obtain a third substance; Step 4, mixing the third substance and polyacrylonitrile, emulsifying, to obtain a fourth substance; Step 5, mixing the fourth substance and polyvinyl alcohol, emulsifying, and obtaining a slurry; The emulsification conditions in step 1 to step 3 are: stirring at 50 to 60° C. and vacuum environment for 15 to 30 minutes, and the emulsification conditions in step 4 to step 5 are: stirring at 50 to 60° C. and vacuum environment for 20 to 30 minutes.
8. The method according to claim 7, characterized in that The ratio of water, polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol is (1600-2400):(1-5):(1-5):(160-180):(180-200):(180-200).
9. The application of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol to synergistically improve the wettability / liquid absorption rate / liquid retention rate of the membrane.
10. The application of polyvinyl pyrrolidone, sodium dodecyl diphenyl ether disulfonate, sodium carboxymethyl cellulose, polyacrylonitrile and polyvinyl alcohol to synergistically improve the ionic conductivity of the membrane.
Citation Information
Patent Citations
Battery diaphragm and preparation method thereof, and lithium ion battery
CN109428035A
Oxide solid electrolyte dispersion liquid as well as preparation method and application thereof
CN116525926A
Coating slurry as well as preparation method and application thereof
CN118496721A
Process for preparing dye-containing, aqueous polymer dispersions
DE19805121A1
Cathode Slurry for Secondary Battery Comprising Dispersing Agent with Excellent Dispersibility and Secondary Battery Comprising the Same
KR1020150025665A